Differentiation and Articulation in Tertiary Education Systems : A Study of Twelve African Countries - Ng'ethe, Njuguna (Washington, DC : World Bank, 2012)
This study strives to sketch an initial map of the extent and nature of institutional and program differentiation within African systems of tertiary education. In doing so, it also seeks to chart the patterns of articulation that have emerged or been consciously put in place between the different institutional types (such as public universities, private universities, polytechnics, training colleges). The analysis of tertiary education differentiation and articulation is based on field visits to a dozen selected African countries. Its purpose is to improve general understanding of this under-researched but strategically important technical aspect of African higher education at a time when it is becoming an important aspect of education policy. African countries display far more differentiation than articulation within their tertiary education systems. Their systems are quite diverse and can be classified as unitary, binary, trinary, semi-differentiated or fully differentiated, depending upon the number of different institutional types that comprise the tertiary system. In general, the polytechnic subsystems appear relatively undifferentiated in comparison to the university sub-systems.